
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


1) (x^2 + x)^2 - (x^2 + x) - 2 = 0
<=> x^2(x + 1)^2 - x^2 - x - 2 = 0
<=> x^4 + 2x^3 + x^2 - x^2 - x - 2 = 0
<=> x^4 + 2x^3 - x - 2 = 0
<=> x^3(x + 2) - (x + 2) = 0
<=> (x^3 - 1)(x + 2) = 0
<=> x^3 - 1 = 0 hoặc x + 2 = 0
<=> x = 1 hoặc x = -2

1 ) x3 - 2x2 + x
= x( x2 - 2x + 1 )
= x ( x-1)2
2) 4x3 - 25x
= x ( 4x2 - 25)
= x( 2x-5) ( 2x +5)
11) \(x^2-y^2-4x+4\)
\(=\left(x^2-4x+4\right)-y^2\)
\(=\left(x-2\right)^2-y^2\)
\(=\left(x-y-2\right)\left(x+y-2\right)\)
13) \(x^4+4=x^4+4x^2+4-4x^2\)
\(=\left(x^2+2\right)^2-4x^2\)
\(=\left(x^2-2x+2\right)\left(x^2+2x+2\right)\)

a, \(4x\left(x-5\right)-7x\left(x-4\right)+3x^2=12\)
\(\Leftrightarrow4x^2-20x-7x^2+28x+3x^2=12\)
\(\Leftrightarrow8x=12\)
\(\Leftrightarrow x=\dfrac{3}{2}\)
Vậy...
b, \(-3x\left(x-5\right)+5\left(x-1\right)+3x^2=4-x\)
\(\Leftrightarrow-3x^2+15x+5x-5+3x^2=4-x\)
\(\Leftrightarrow21x=9\)
\(\Leftrightarrow x=\dfrac{3}{7}\)
Vậy...
c, \(\left(x-5\right)\left(x-4\right)-\left(x+1\right)\left(x-2\right)=7\)
\(\Leftrightarrow x^2-9x+20-x^2+x+2=7\)
\(\Leftrightarrow-8x=-15\Leftrightarrow x=\dfrac{15}{8}\)
Vậy...
d, \(-\left(x+3\right)\left(x-4\right)+\left(x-1\right)\left(x+1\right)=10\)
\(\Leftrightarrow-x^2+x+12+x^2-1=10\)
\(\Leftrightarrow x=-1\)
Vậy...
e, \(\left(x-3\right)\left(x^2+3x+9\right)+x\left(5-x^2\right)=6x\)
\(\Leftrightarrow x^3-27+5x-x^3=6x\)
\(\Leftrightarrow x=-27\)
Vậy...
a) \(4x\left(x-5\right)-7x\left(x-4\right)+3x^2=12\)
\(4x^2-20x-7x^2+28x+3x^2-12=0\)
\(8x-12=0\)
\(4\left(2x-3\right)=0\)
\(2x-3=0\Rightarrow x=\dfrac{3}{2}\)
b) \(-3x\left(x-5\right)+5\left(x-1\right)+3x^2=4-x\)
\(-3x^2+15x+5x-5+3x^2-4+x=0\)
\(21x-9=0\)
\(3\left(7x-3\right)=0\)
\(\Rightarrow7x-3=0\Rightarrow x=\dfrac{3}{7}\)
c) \(\left(x-5\right)\left(x-4\right)-\left(x-1\right)\left(x-2\right)=7\)
\(x^2-4x-5x+20-x^2+2x+x-2-7=0\)
\(-6x+11=0\Rightarrow x=\dfrac{11}{6}\)
d) \(-\left(x-3\right)\left(x-4\right)+\left(x-1\right)\left(x+1\right)=10\)
\(-x^2+4x+3x-12+x^2-1-10=0\)
\(7x-23=0\)
\(x=\dfrac{23}{7}\)
e) \(\left(x-3\right)\left(x^2+3x+9\right)+x\left(5-x^2\right)=6x\)
\(x^3-27+5x-x^3-6x=0\)
\(-x-27=0\Rightarrow x=-27\)

a)x^3 - 3x^2 + 4x - 12
= x^2(x - 3) + 4(x - 3)
= (x - 3)(x^2 + 4)

\(x\left(x-3\right)+x-3=0\)
\(\left(x-3\right)\left(x+1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-3=0\\x+1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=3\\x=-1\end{cases}}}\)
KL:......................
\(x^3-5x=0\)
\(x\left(x^2-5\right)=0\)
Làm tương tự như câu a
@_@ n...h..i......ề....u q...u.....................á!
1/ x2 + x - 12
= ( x2 + x ) - 12
= x( x + 1 ) - 12
= ( x - 12 )( x + 1)
2/ x2 + 3x - 4
= ( x2 + 3x ) - 4
= x( x + 3 ) - 4
= (x - 4)(x + 3)
x^2 +x-12 = x^2-3x+4x-12
= (x^2-3x)+(4x-12)
=x(x-3)+4(x-3)
=(x+4)(x-3)
x^2+3x-4 = x^2-x+4x-4
=(x^2-x)+(4x-4)
=x(x-1)+4(x-1)
=(x+4)(x-1)